2012
DOI: 10.1364/ol.37.002439
|View full text |Cite
|
Sign up to set email alerts
|

DAST/SiO_2 multilayer structure for efficient generation of 6 THz quasi-single-cycle electromagnetic pulses

Abstract: We propose a DAST∕ SiO 2 multilayer structure for efficient generation of near-single-cycle THz transients with average frequency around 6 THz via collinear optical rectification of 800 nm femtosecond laser pulses. The use of such a composite material allows compensation for the phase mismatch that accompanies THz generation in bulk DAST crystals. The presented calculations indicate a strong increase in the THz generation efficiency in the DAST∕ SiO 2 structure in comparison to the case of bulk DAST crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…The use of a DAST/SiO 2 multilayer structure allows employing the 111 OR  = 1230 pV/m of DAST [21] at 0.8 m which is significantly higher than that at 1.5 m (490 pV/m) [21]. In a previous paper [18], it was speculated that the use of femtosecond laser pulses at 800 nm rather than two monochromatic waves would provide generation of near-single-cycle THz pulses in a DAST/SiO 2 multilayer structure. However, the time profiles and spectra of THz pulses obtained with this method were not explicitly shown.…”
mentioning
confidence: 92%
“…The use of a DAST/SiO 2 multilayer structure allows employing the 111 OR  = 1230 pV/m of DAST [21] at 0.8 m which is significantly higher than that at 1.5 m (490 pV/m) [21]. In a previous paper [18], it was speculated that the use of femtosecond laser pulses at 800 nm rather than two monochromatic waves would provide generation of near-single-cycle THz pulses in a DAST/SiO 2 multilayer structure. However, the time profiles and spectra of THz pulses obtained with this method were not explicitly shown.…”
mentioning
confidence: 92%
“…It was found that in order to obtain a high pump-to-THz energy conversion efficiency (up to 2% [16]) in many organic salt crystals, the application of femtosecond laser pulses at 1.2−1.5 m is required. Alternatively the use of a DAST/SiO 2 multilayer structure for efficient generation of near single cycle pulses with an average frequency of 6 THz via collinear optical rectification of 800 nm femtosecond laser pulses was proposed [20].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that in order to obtain a high pump-to-THz energy conversion efficiency (up to 2% [14]) in many organic salt crystals, the application of femtosecond laser pulses at 1.2−1.5 µm is required. The use of a DAST/SiO 2 multilayer structure for efficient generation of near single cycle pulses with an average frequency of 6 THz via collinear optical rectification of 800 nm femtosecond laser pulses was also proposed [18].…”
Section: Introductionmentioning
confidence: 99%